An Extension of the J‐Test to a Spatial Panel Data Framework. (5th January 2015) - Kelejian, Harry H.; Piras, Gianfranco
Summary: Kelejian ( Letters in Spatial and Resources Sciences ;1 : 3–11) extended the J ‐test procedure to a spatial framework. Although his suggested test was computationally simple and intuitive, it did not use the available information in an efficient manner. Kelejian and Piras ( Regional Science and Urban Economics ;41 : 281–292) generalized and modified Kelejian's test to account for all the available information. However, neither Kelejian (2008 ) nor Kelejian & Piras (2011 ) considered a panel data framework. In this paper we generalize these earlier works to a panel data framework with fixed effects and additional endogenous variables. We give theoretical as well as Monte Carlo results relating to our suggested tests. An empirical application on a crime model for North Carolina is also estimated. Copyright © 2015 John Wiley & Sons, Ltd.